Is contractual flexibility always good for relationship quality among the parties in construction projects? - Ding, Qianxing; Zhang, Lianying; Yiu, Tak Wing; Liu, Ziqing (Journal of Civil Engineering and Management, 2025)
Contractual flexibility as an effective way to maintain and increase parties’ relationship quality has been widely introduced to contracting in construction projects. However, conflicting evidences exist regarding their effectiveness on relationship quality based on transaction cost theory. Building on two distinct bases for contractual flexibility: content flexibility, rely on flexible content incorporated in initial contract content, versus executing flexibility, rely on parties’ relationship instead of contract contents, this study examines how contractual flexibility effect relationship quality under different transaction attributes (asset specificity, environmental uncertainty, and behavioral uncertainty). Results from a sample of 312 parties reveal that content flexibility and executing flexibility positively influence relationship quality, with executing flexibility having a stronger association than content flexibility. Yet, important conditions exist. The moderating analysis demonstrates that when asset specificity or environmental uncertainty is high, executing flexibility, not content flexibility, matters more to relationship quality. In contrast, when behavioral uncertainty is high, content flexibility, not executing flexibility, matters more to relationship quality. These findings suggest that contractual managers should incorporate executing flexibility into contracts more sufficiently, and the appropriate contractual flexibility should match with transaction attributes.